Chromosomal and Genomic Dynamics of Satellite DNAs in Characidae (Characiformes, Teleostei) Species - Rodrigues, Pedro Henrique De Mira [UNESP]; Dos Santos, Rodrigo Zeni [UNESP]; Silva, Duílio Mazzoni Zerbinato De Andrade [UNESP]; Goes, Caio Augusto Gomes [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP]; Utsunomia, Ricardo [UNESP] (SAGE Publications, 2019)
Satellite DNAs (satDNAs) are tandemly repeated DNA sequences with great abundance in eukaryotic genomes. A single species may carry up to hundreds of satDNA families, which is collectively called as satellitome, each showing its own dynamics and evolution rates. In this context, all live species contain a satDNA library that may be partially or totally shared with other related species/populations. In the late few years, next-generation sequencing (NGS) and novel bioinformatic tools facilitated the massive characterization of these sequences at low costs, and consequently, comparing satDNAs between species. In this study, we characterized two novel satDNAs (MsaSat03-80 and MsaSat04-142) in three characid fish (Astyanax paranae and Astyanax fasciatus and two populations of Moenkhausia sanctaefilomenae) and mapped their chromosomal location to unveil the evolutionary dynamics of satDNA repeats in those species. Our results evidenced that MsaSat03 is present in the genomes of all analyzed species, but is clustered only in the chromosomes of M. sanctaefilomenae, exhibiting a conserved number and location of sites. Conversely, MsaSat04 sequences is restricted to M. sanctaefilomenae and shows a differential distribution between the two analyzed populations. Altogether, our analyses point to a complex history of satDNA families in characid fish and the utility of NGS data for comparative satDNA analysis.
Keywords: Astyanax; concerted evolution; Moenkhausia; repetitive DNA; Teleostei